Low fermentable oligosaccharides, disaccharides, monosaccharides, and polypols diet and irritable bowel syndrome in Asia. Issue 2 (28th December 2018) - Zhang, Yihe; Ma, Zheng Feei; Zhang, Hongxia; Pan, Binyu; Li, Yeshan; Majid, Hazreen A; Lee, Yeong Yeh
Abstract : Functional bowel disorders, including irritable bowel syndrome (IBS), are a chronic condition that can significantly reduce patients' quality of life. Therefore, this paper will review the roles of a low fermentable oligosaccharides, disaccharides, monosaccharides, and polypols (FODMAP) diet in treating IBS, particularly in an Asian setting. About 20% of the general population is diagnosed with IBS. However, there are limited effective medical therapies available for treating IBS. Therefore, IBS presents a major challenge to the health‐care providers. Recently, there is an increasing interest in the use of a diet low in FODMAP for the treatment of IBS. A low FODMAP diet can decrease the delivery of readily fermentable substrates to the small intestine and colon, thereby improving functional gastrointestinal symptoms. Abstract : Functional bowel disorders, including irritable bowel syndrome (IBS), are chronic conditions that can significantly reduce patients' quality of life. Therefore, this paper will review the roles of a low fermentable oligosaccharides, disaccharides, monosaccharides, and polypols diet in treating IBS, particularly in an Asian setting.